Carry‐over effects and fitness trade‐offs in marine life histories: The costs of complexity for adaptation. (20th September 2022) - Marshall, Dustin J.; Connallon, Tim
Abstract: Most marine organisms have complex life histories, where the individual stages of a life cycle are often morphologically and ecologically distinct. Nevertheless, life‐history stages share a single genome and are linked phenotypically (by "carry‐over effects"). These commonalities across the life history couple the evolutionary dynamics of different stages and provide an arena for evolutionary constraints. The degree to which genetic and phenotypic links among stages hamper adaptation in any one stage remains unclear and yet adaptation is essential if marine organisms will adapt to future climates. Here, we use an extension of Fisher's geometric model to explore how both carry‐over effects and genetic links among life‐history stages affect the emergence of pleiotropic trade‐offs between fitness components of different stages. We subsequently explore the evolutionary trajectories of adaptation of each stage to its optimum using a simple model of stage‐specific viability selection with nonoverlapping generations. We show that fitness trade‐offs between stages are likely to be common and that such trade‐offs naturally emerge through either divergent selection or mutation. We also find that evolutionary conflicts among stages should escalate during adaptation, but carry‐over effects can ameliorate this conflict. Carry‐over effects also tip the evolutionary balance in favor of better survival in earlier life‐history stages at the expense of poorer survival in later stages. This effect arises in our discrete‐generation framework and is, therefore, unrelated to age‐related declines in the efficacy of selection that arise in models with overlapping generations. Our results imply a vast scope for conflicting selection between life‐history stages, with pervasive evolutionary constraints emerging from initially modest selection differences between stages. Organisms with complex life histories should also be more constrained in their capacity to adapt to global change than those with simple life histories.